Detail Experimental Procedure for the Construction Process of Robotic Devices to Teach Aspect of Auto Mechanic - Ebenezer Omolafe Babalola; Eyiyemi Veronica Omolafe (Universitas Pendidikan Indonesia (UPI), 2022)
Construction involves the translation of a design into reality, this involves a systematic and conscientious process of bringing together or assembling diverse elements or parts to form a whole. Therefore, special care has to be taken during construction as the design intentions must be achieved. The construction of a robotic instructional model is a task that can be engaged by an expert in the area of Instructional Technology. It requires several practices and devotion to the principles and use of elements of design. Also, the appropriate use of relevant tools, equipment, and tools is indispensable. However, for an interested individual, skills for model construction can be acquired by first having an adequate observational view of the real objects to get familiar with the forms and features of the object. Robotic instructional devices can exhibit gestures and body movements so they could be used by the teacher to explain a concept. Robots can create an interactive and engaging learning experience. The important factors that influence whether the robot is likely to be useful in teaching include usability and the availability of appropriate learning activities and content. There is a need of implementing some content of the curriculum through robotic devices. In the light of this view, this study shows the detailed experimental procedure for the construction process of robotic devices to teach an aspect of Auto Mechanic in Nigerian basic schools.